Pandemic metaphors: bibliometric study of the COVID-19 (co)llateral effects (Research, Society and Development, 2020)
The objective of this study is to analyze the (co)llateral effects of the pandemic in a general aspect, showing positive and negative effects. However, highlighting marked changes to the environment, given the time when the emission of carbon dioxide into the atmosphere received a mandatory reduction as a result of social confinement. The methodological basis used is a systematic literature review, consulted in impact databases by the scientific community. We chose to search the Web of science, Science Direct and PubMed databases. The search keys were: pandemic, COVID-19, new coronavirus, effects of COVID-19. In addition, to analyze the presence of conceptual metaphors, opinion articles published in the world media, and published on the web during a pandemic were selected. The choice of texts is based on the theme of the new coronavirus and its impacts. The theoretical bias of Lakoff (1987; 2006) is adopted to explain metaphor on the cognitive plane, as a natural process of the human mind, that is, a way of thinking. This research is characterized in qualitative, bibliographic and analysis of content. The results show that the conceptual metaphors reveal an image of COVID-19 as the "savior" of the environment, for having forced man to stop as a need for carbon. It was concluded that the conceptual metaphors, being of a cognitive nature, appear in the form discourse, showing COVID-19 as agents of positive effects on the environment and business for the other areas of society.